Rectal mobilization: the place of Denonvilliers' fascia and inconsistencies in the literature. (October 2016) - Chapuis, P. H.; Kaw, A.; Zhang, M.; Sinclair, G.; Bokey, L.
Abstract: Confusion remains as to what is meant by Denonvilliers' fascia. This review searched the literature on pelvic surgical anatomy to determine whether there is agreement with Denonvilliers' original description and its implication in defining the correct anterior plane of dissection when mobilizing the rectum. The original French description of the fascia was translated into English and then compared both with French and with English studies identified by searching PubMed, Medline and Scopus from 1836 to June 2015. Special emphasis was given to the years between 1980 and 2015 in order to capture the literature pertinent to, and following on from, the description of total mesorectal excision for rectal cancer. The final literature search revealed 16 studies from the original 2150 citations. Much of the debate was concerned with the origin and development of the fascia, arising from either the 'fusion' or the 'condensation' of local primitive tissue into a mature 'multilayered' structure. Controversy regarding the correct plane of rectal mobilization occurs as a result of different interpretations by surgeons, anatomists and radiologists and bears little resemblance to Denonvilliers' original description. This may reflect wide anatomical variability in the adult pelvis or a form of dissection artefact. Further study is required to investigate this. Logically, for both men and women, the plane of rectal mobilization should be behind Denonvilliers' fascia and between it and the fascia propria of the rectum.